2018
DOI: 10.1039/c8ra01833b
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of cellular morphologies and crystalline structures in high-expansion isotactic polypropylene/cellulose nanofiber nanocomposite foams

Abstract: Herein, the development of cell morphology and crystalline microstructure of injection-molded isotactic polypropylene/cellulose nanofiber (PP/CNF) composite foams with 2-10-fold expansion ratios was investigated through scanning electron microscopy (SEM), wide-angle X-ray diffraction (WAXD), and small-angle X-ray scattering (SAXS). Compared with isotactic polypropylene (iPP) foams, the added CNF improved the cell morphology and resulted in a great reduction in cell size. Additionally, the PP lamella orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 65 publications
2
58
0
Order By: Relevance
“…These mechanical properties depended on the degree of substitution (DS) and were maximized at the optimal DS value of 0.44. Wang et al studied the foaming of ASA‐CNF/isotactic polypropylene (iPP) composites 18–22 . They confirmed the formation of a network‐like structure of CNFs in the iPP matrix by rheological measurements and achieved an 18‐fold expansion ratio by combining the materials with a core‐back injection molding process.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanical properties depended on the degree of substitution (DS) and were maximized at the optimal DS value of 0.44. Wang et al studied the foaming of ASA‐CNF/isotactic polypropylene (iPP) composites 18–22 . They confirmed the formation of a network‐like structure of CNFs in the iPP matrix by rheological measurements and achieved an 18‐fold expansion ratio by combining the materials with a core‐back injection molding process.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, the foam injection molding (FIM) using supercritical fluid (SCF) as a physical blowing agent has been investigated in the way of ecofriendly foaming technology 9 . This method is widely studied with various thermoplastics, for instances, PP, 5,10–15 high‐density polyethylene, 16 acrylonitrile butadiene styrene, 17 and poly(lactic acid) (PLA), 18 and the mechanical, morphological, and thermal properties of their foams are also evaluated. However, the foamability of PP is poor due to the low melt strength and lack of strain hardenings, which can lead to the cell breakings and coalescences 18–20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the foamability of PP is poor due to the low melt strength and lack of strain hardenings, which can lead to the cell breakings and coalescences 18–20 . PP modified by various fibers and particles, such as carbon fiber (CF), 5,7,8 glass fiber (GF), 10 talc, 11 and natural fibers, 12,13 have been reported that the melt strength and cell nucleation can be improved. Furthermore, the incorporation between general PP and long chain branching 14,20–22 or crosslinking 22,23 PP could generate strain hardening and suppress the cell breakings and coalescences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations